Financial Literacy as A Moderating Variable in Influencing Individual Income, Cashless Use, and Love of Money on Financial Behavior of STIEM Bongaya Students - Andi Rachmat Fiqra Asapa; Syamsul Alam; I. Ishak (Golden Ratio of Auditing Research, 2026)
This study aims to explore the impact of individual income, cashless payment system utilization, and love of money on college students' financial behavior, with financial literacy as a variable strengthening this relationship. The respondents in this study were students from STIEM Bongaya. The analysis method used was Partial Least Squares (PLS) with a measurement model and structural model approach. The findings from the test indicate that individual income and financial literacy have a significant positive impact on college students' financial behavior. Conversely, cashless use and love of money do not show a significant influence on financial behavior. Furthermore, financial literacy does not function as a moderating variable in the relationship between individual income, cashless use, and love of money on financial behavior. The R-square value of 0.662 indicates that the independent and moderating variables can explain 66.2% of financial behavior, while the Q-square value of 0.541 indicates that this model has good predictive relevance. The implications of this study indicate the need to improve financial literacy among university students through well-designed educational programs to foster prudent and responsible financial attitudes. Future research is recommended to incorporate other variables, such as psychological and social factors, or the use of financial technology (fintech) to predict financial behavior.